THE EFFECT OF VITAMIN E (α- TOCOPHEROL) AS NEPHROPROTECTOR ON BLOOD UREA NITROGEN AND SERUM CREATININE LEVEL OF STRAIN WISTAR RATS AFTER CISPLATIN TREATMENT: IN VIVO STUDY - Affandi, Yohan; Djatisoesanto, Wahjoe; Hakim, Lukman (Indonesian Urological Association, 2020)
Objective: To analyze the differences in kidney function of Wistar strain rats that received a combination of vitamin E and cisplatin, compared with cisplatin alone. Material & Methods: An experimental prospective study with post-test only control design, using male Wistar strain rats (Rattus norvegicus). Rats were randomized using the simple randomized sampling method. Treatment was given in the form of exposure to cisplatin 5 mg/kg (positive control group), with a combination of vitamin E 100 mg/kg and 200 mg/kg (treatment group), to evaluate its effect on kidney function as measured by blood urea nitrogen (BUN) and creatinine serum. Results: Statistical analysis of Mann Whitney showed that there were no differences in BUN levels in the positive control group (cisplatin 5 mg/kg) against each treatment group (p>0.05). Further analysis showed that there was no significant difference between treatment group 1 (Vitamin E 100 mg/kg) and treatment group 2 (Vitamin E 200 mg/kg). There was no difference in serum creatinine levels in the positive control group compared to a treatment group that received both vitamin E 100 mg/kg and the vitamin E 200 mg/kg (p>0.05). further analysis revealed no significant difference in serum creatinine levels between the group that receives vitamin E 100 mg/kg and 200 mg/kg. Conclusion: Vitamin E at doses of 100 mg/kg and 200 mg/kg did not have the nephroprotective feature in cisplatin-exposed Wistar rats.